2016
DOI: 10.1186/s13019-016-0407-1
|View full text |Cite
|
Sign up to set email alerts
|

Is preoperative protein-rich nutrition effective on postoperative outcome in non-small cell lung cancer surgery? A prospective randomized study

Abstract: ObjectiveProtein-rich nutrition is necessary for wound healing after surgery. In this study, the benefit of preoperative nutritional support was investigated for non-small cell lung cancer patients who underwent anatomic resection.MethodsA prospective study was planned with the approval of our institutional review board. Fifty-eight patients who underwent anatomic resection in our department between January 2014 and December 2014 were randomized. Thirty-one patients were applied a preoperative nutrition progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 19 publications
0
42
0
1
Order By: Relevance
“…A táplálásterápiában részesülők körében kevesebb volt a műtét utáni komplikációk aránya (10,3% vs. 44,4%; p = 0,049). A szerzők javasolták, hogy a műtét utáni albuminszint normális tartományban tartásához (≥35 g/l) a preoperatíve mért <45 g/l albuminszint esetén táplálásterápia bevezetését tartották szükségesnek [71]. Figyelemre méltó, hogy lokalizált rosszindulatú daganatos betegségekben a normális BMI-érték melletti alacsony albuminszint rossz prognózist vetít előre, míg a BMI-értéknek az esetek nagyobb részében nincs prognosztikus értéke [25,31,32,34,37].…”
Section: öSszefoglaló Közleményunclassified
“…A táplálásterápiában részesülők körében kevesebb volt a műtét utáni komplikációk aránya (10,3% vs. 44,4%; p = 0,049). A szerzők javasolták, hogy a műtét utáni albuminszint normális tartományban tartásához (≥35 g/l) a preoperatíve mért <45 g/l albuminszint esetén táplálásterápia bevezetését tartották szükségesnek [71]. Figyelemre méltó, hogy lokalizált rosszindulatú daganatos betegségekben a normális BMI-érték melletti alacsony albuminszint rossz prognózist vetít előre, míg a BMI-értéknek az esetek nagyobb részében nincs prognosztikus értéke [25,31,32,34,37].…”
Section: öSszefoglaló Közleményunclassified
“…Thirty-five percent of patient in the experimental group and 40% in the control group were operated with VATS technique. This study showed that preoperative nutrition was beneficial in decreasing the complication rate (19% vs. 44%) and mean chest tube removal time (4 vs. 6 days) (15).…”
Section: Patient Optimisation For Comorbidities and Risk Factorsmentioning
confidence: 68%
“…Furthermore, patients at risk for adverse outcomes may potentially be identified preoperatively permitting prehabilitative and perioperative nutritional interventions to be implemented accordingly. Surgical rehabilitation includes the use of aerobic and resistant exercises and nutritional optimization to a preoperative albumin of >4 g/dl to improve postoperative outcomes [33,34]. In a recent randomized control trial, preoperative nutritional interventions were compared in patients undergoing colorectal resection [35].…”
Section: Discussionmentioning
confidence: 99%